INSTRUCTING TOURISM TERMS APPLYING INFORMATION TECHNOLOGY - Teacher: Nishanova Xafiza Vafokulovna (American Journals, 2023)
Information technologies (IT) at present are influencing every aspect of human life. They are playing salient roles in work places, business, education, and entertainment. Moreover, many people recognize ITs as catalysts for change; change in working conditions, handling and exchanging information, teaching methods, learning approaches, scientific research, and in accessing information technologies. In this digital era, IT use in the classroom is important for giving students opportunities to learn and apply the required 21st century skills. IT improves teaching and learning and its importance for teachers in performing their role of creators of pedagogical environments.
Keywords: Information technology, education, terms, learning